2014
DOI: 10.1002/hep.26782
|View full text |Cite
|
Sign up to set email alerts
|

An effective interferon-gamma-mediated inhibition of hepatitis C virus replication by natural killer cells is associated with spontaneous clearance of acute hepatitis C in human immunodeficiency virus-positive patients

Abstract: Hepatitis C virus (HCV) coinfection is an increasing health problem in human immunodeficiency virus‐positive (HIV+) individuals. However, a considerable proportion of HIV+ patients manage to overcome acute hepatitis C (AHC) spontaneously. In the present study, we analyzed the role of natural killer (NK) cells in modulating the course of AHC in HIV+ patients. Twenty‐seven HIV+ patients with AHC (self‐limited course: n = 10; chronic course: n = 17), 12 HIV+ patients with chronic hepatitis C (CHC), 8 HIV monoinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 37 publications
0
39
0
7
Order By: Relevance
“…These features persisted in the postacute period, but most functions resolved to baseline levels by the time of virus clearance. Empirical HCV studies suggest that enhanced NK cell function during acute infection can lead to viral containment (46)(47)(48), and in persons accidentally exposed to HCV, NK cells exert upregulated effector functions (36). Collectively, these data may suggest that the robust NK cell response we observed in acute GBV-B infection is related to the virus clearance normally observed (40,49).…”
Section: Discussionmentioning
confidence: 63%
“…These features persisted in the postacute period, but most functions resolved to baseline levels by the time of virus clearance. Empirical HCV studies suggest that enhanced NK cell function during acute infection can lead to viral containment (46)(47)(48), and in persons accidentally exposed to HCV, NK cells exert upregulated effector functions (36). Collectively, these data may suggest that the robust NK cell response we observed in acute GBV-B infection is related to the virus clearance normally observed (40,49).…”
Section: Discussionmentioning
confidence: 63%
“…In these cases, protected individuals had an increased frequency of NK cells, as well as increased IFNγ production and cytotoxicity. In co-culture experiments, it was shown that NK cells inhibit HCV replication by secreting IFNγ 55,56 . In particular, NKp46 high NK cells efficiently suppressed HCV replication 57,58 .…”
Section: Natural Killer Cellsmentioning
confidence: 98%
“…Chronic exposure to type I IFNs increases STAT1 expression in NK cells, which results in STAT1 dominance over STAT4 in intracellular signalling pathways 62,63 . As a consequence, NK cells upregulate expression of the apoptosis-inducing ligand TRAIL (also known as TNFSF10) and have increased cyto toxicity, whereas they have decreased IFNγ production 62,63 , which is an important effector function of NK cells for HCV control 56 .…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…While the exact mechanisms underlying these distinct immune activation profiles are not well understood, previous studies have suggested some crucial roles of these genes, such as the elevation of CX3CL1 as a marker of liver fibrosis/injury [29], TGF-β as a potent inducer of fibrogenesis [26], and interferon-α inhibiting HCV replication [42]. Interestingly, a recent study has reported that an effective interferon-γ mediated inhibition of HCV replication by NK cells is associated with spontaneous clearance of HCV in HIV+ patients [43], which is in line with our simultaneous detections of both the dysregulation of NK cytotoxicity pathway and the decreased expression of IFNG in co-infected individuals.…”
Section: Discussionmentioning
confidence: 99%